EFEKTIFITAS PEMBERIAN PERMEN JAHE TERHADAP MUAL MUNTAH PADA IBU HAMIL DI RUMAH SAKIT UMUM DAERAH RAJA AHMAD TABIB TANJUNGPINANG - Elena, Elena; Sihombing, Sarmauli Franchisca; Fahnawal, T. Marzila (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2021)
Nausea and vomiting that occur in pregnancy are caused by an increase in the hormones estrogen and progesterone produced by HCG in serum from the placenta. In emesis gravidarum, if not treated immediately, it will result in weight loss due to inadequate maternal nutritional intake resulting in increased incidence of fetal growth disorders, low birth weight, and congenital defects in the fetus. The purpose of the study was to determine the effectiveness of giving ginger candy to nausea and vomiting in pregnant women. The research method is Quasy experimental with "One group pretest posttest design" design. The population is 30 people. Sampling was done by purposive sampling. The data were analyzed using the T-test. The results showed that the effectiveness of giving ginger candy to nausea and vomiting in pregnant women from the test results using the t-test obtained a p-value of 0.000 (p <0.05) thus Ha received an increase in the average value before being given treatment 10.83 and after being given the mean value of treatment is 7.27, from these data it can be concluded that there is a significant difference between the scores of nausea and vomiting before and after being given ginger candy. The conclusion of this study is that there is an effect of ginger candy on nausea and vomiting in pregnant women.